The floristic quality assessment index as ecological health indicator for forest vegetation: A case study from Zabarwan Mountain Range, Himalayas. (December 2022) - Haq, Shiekh Marifatul; Amjad, Muhammad Shoaib; Waheed, Muhammad; Bussmann, Rainer W.; Proćków, Jarosław
Highlights: Floristic Quality Assessment Index (FQAI) is used to evaluate the e health status of the vegetation. Of the 54 alien species, thirteen species were invasive, 36 were naturalized, and five were casual. The largest (38%) species pool was observed in natural forest habitats. Broadleaved forest harbored most alien species (35%) as compared to other types. FAQI is best for measuring vegetation communities' responses to alien invasions. Abstract: Evaluations ecosystem health-based field studies can assist decision-makers in formulating more targeted conservation policies to better manage ecosystems and landscape. To analyze forest characteristics in the Zabarwan Mountain Range we used the Floristic Quality Assessment Index (FQAI) technique to evaluate the ecosystem health status of the vegetation. According to our findings, the forest area showed an FQAI rating of 61.41. The FQAI ranked 54 of the plant species growing in the forest region at 0, 30 species at 1–3, 51 species at 4–6, 30 species at 7–8, and 17 species at 9–10. Of the 54 alien species ranking 0, thirteen species were invasive, 36 were naturalized, and five were casual. Amoung the forest types, the Broadleaved forest harbored most alien species (35%) and the scrub forest the least (6%). Based on habitat-wise distribution, the largest (38%) species pool was observed in natural forest habitats, while human-modified habitat types harbord 51% of species. Roadsides exhibited the by far highest alien species number (45%) together with other anthropogenic habitats. The investigation of indicator species revealed a separation between the various ranking groups, as evidenced by high indicator values. Important alien indicator species ranking 0 were i.e., Aesculus indica, Ailanthus altissima, Celtis australis, Daucus carota, Poa bulbosa, Prunus armeniaca, Prunus cerasus, Quercus robur, and Salix alba, which showed a significant p-value for indicator species analysis. The findings of this study provide a method for measuring vegetation communities' responses to alien invasions and as a result can serve for developing management methods to preserve ecosystems, particularly in protected areas, from this biodiversity threat.